PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, SALES GROWTH, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - KEVIN HONGGO; AAN MARLINAH (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this research is to examine the influence of firm size, firm age, council independent commissioner, audit committee, sales growth, and leverage on tax avoidance at manufacturing companies listed in Indonesia Stock Exchange (IDX). The population of this research is all manufactured companies listed inIndonesia Stock Exchange from 2014 to 2016. Samples are obtained through purposive sampling method, in which only 60 of listed manufactured companies in Indonesia Stock Exchange meet the sampling criterias resulting 180 data available are taken as the samples. The research resources are taken from Indonesia Stock Exchange website. This research used multiple regression method to test the effect of each variable in influencing tax avoidance. From this research the test results indicates that firm size, and sales growth have influence to tax avoidance. However firm age, council independent commissioner, audit committee, and leverage have no influence to tax avoidance.